Addressing knowledge gaps: the key role of community health workers and healthcare providers in human papillomavirus prevention and vaccine uptake in a border community - Moya, Eva M.; Garcia, Araceli; Joyce Ponder, Amy; Frietze, Gabriel (Frontiers in Public Health, 2023)
The Human Papillomavirus (HPV) is the most common sexually transmitted infection and nearly every person who is sexually active will get HPV at some point in their lifetime without having the HPV vaccine. Healthcare Providers (HCPs) and Community Health Workers (CHWs) play an essential role in promoting the HPV vaccine and providing education about HPV in communities. Three focus groups with CHWs (n=17) and HCPs (n=7) were conducted and led by trained facilitators. In addition to participating in the focus group, CHWs and HCPs completed a brief questionnaire. Focus groups were voice recorded and transcribed for qualitative analysis. Independent coders conducted content analysis to identify the salient themes of the focus groups. Several important findings emerged from this study highlighting the barriers to HPV knowledge, gaps in the self-perceived role of HPV cancer prevention, and opportunities to action. Financial, knowledge, patriarchy, behaviors, attitudes, and fears were identified as the perceived patient-related barriers to promoting HPV cancer prevention. Both CHWs and HCPs explained that their female patients are often discouraged by their husbands from seeking out sexual health-related healthcare. Finding suggest the need for community tailored education on HPV and "best practice" trainings for HPV prevention that is applicable to both CHWs and HCPs.